Plasma‐thrombin cell blocks: Potential source of DNA contamination. Issue 12 (22nd November 2019) - Sung, Simon; Sireci, Anthony N.; Remotti, Helen E.; Hodel, Vaishali; Mansukani, Mahesh M.; Fernandes, Helen; Saqi, Anjali
Abstract : Background: Cell blocks are being used more frequently in cytology for ancillary testing, including molecular diagnostics. There are several different methods of processing cell blocks, with plasma‐thrombin being one of the most common. Plasma is a blood‐derived product and may be a source of DNA. The aim of this study was to determine whether the plasma used for the plasma‐thrombin cell block method has amplifiable DNA that may potentially interfere with molecular testing results. Methods: Expired bags of fresh frozen plasma were collected from a blood bank. From each sample, DNA was extracted from a 1‐mL aliquot with the QIAsymphony MIDI kit (Qiagen). The concentration of DNA was measured on a NanoDrop instrument. The amplifiable DNA quality was assessed by polymerase chain reaction (PCR) with primers to generate amplicons of various sizes. Characterization was performed with the AmpFLSTR Identifiler Plus PCR kit with capillary electrophoresis. Results: Twenty samples from 20 bags were collected. All samples showed amplifiable DNA despite low DNA concentrations in a few cases. PCR amplification revealed the presence of high‐quality amplifiable DNA (up to 600 base pairs). DNA was amplified at the 16 loci interrogated in all samples tested with the AmpFLSTR Identifiler Plus PCR kit. Conclusions: The presence of genomic DNA in plasma may theoretically interfere with results of molecular testing. Particularly in clinical samples with low cellularity, the DNA in plasma may potentially either mask the presence of minute amounts of tumor‐derived DNA or lead to a false‐positive result. Abstract : The commonly used plasma‐thrombin cell block method may be a source of DNA contamination. This can potentially interfere with molecular testing as molecular techniques advance and become more sensitive.